Innovation's Mediating Contribution To The Relationship Between Financial Flexibility And Sustainability Performance - Rahmadhani, Sari; Praptitorini, Mirna Dyah; Shobandiyah, Siti; Laila, Nazil Rizki (KEUNIS, 2025)
This study explores the impact of debt and cash combination arrangements as financial flexibility that can improve sustainable performance in companies. This research also examines how innovation mediates the relationship between a company's financial flexibility and future sustainability achievements. Utilizing a resource-based view and path analysis, we analyze data from sustainability reports of basic and chemical industry firms listed on the IDX from 2020 to 2023. These findings provide empirical evidence that contingency theory can adapt by controlling the effect of financial flexibility on sustainability performance. As tested through debt and cash flexibility, financial flexibility has no direct impact on sustainability performance. Meanwhile, innovation is proven to depend on sustainability achievement. Empirical evidence of resource-based theory, where financial flexibility is a potential competitive advantage over the development and research process in innovation. Likewise, innovation holds a significant role in linking financial flexibility to sustainability performance. Companies with flexible finances can more easily allocate resources to innovate, increasing the company's ability to carry out activities that pay attention to the social and environmental impacts of sustainable business activities.